Battenispermum hirsutum gen. et sp. nov., a new Early Cretaceous seed from Portugal with chlamydospermous organisation. (May 2020) - Mendes, Mário Miguel; Pedersen, Kaj Raunsgaard; Friis, Else Marie
Abstract: A new genus and species, Battenispermum hirsutum, is described from the Early Cretaceous mesofossil flora of Catefica, Portugal. The new taxon is based on five ovulate structures with up to three seeds surrounded by an outer cup formed from partly fused bracts. The seeds are small, about 2.4–3.3 mm long and 1.0–1.6 mm wide, orthotropous with a chlamydospermous organisation. The nucellus is surrounded by a thin integument, a sclerenchymatic inner seed envelope and an additional outer envelope of four bracts, fused for most of their length. The seeds are three- or four-angled in transverse section and elliptical in lateral view with the free tips of the outer envelope forming short, apical projections around the micropyle. The outer surface of the inner seed envelope is almost smooth, while the abaxial surfaces of both inner and outer bracts of the compound ovulate structures are covered by a dense indumentum of long and stiff trichomes. Battenispermum hirsutum clearly belongs to the chlamydospermous BEG complex (Bennettitales-Erdtmanithecales-Gnetales), but it is distinguished from all previously described fossils by the presence of two distinct seed envelopes, a feature otherwise known only for extant Gnetum . The seeds of Battenispermum hirsutum differ, from those of extant Gnetum in other features, including the much simpler micropylar region. Highlights: A new chlamydospermous seed is described from the Portuguese Cretaceous. The new taxon Battenispermum hirsutum is distinctive in having two seed envelopes. The new finding adds new information on the morphological variation in BEG seeds. Supports the importance of the BEG group in the Early Cretaceous floras.